Improving Remote Collaboration With Video Conferencing and Video Portals. (2nd January 2016) - Karis, Demetrios; Wildman, Daniel; Mané, Amir
Abstract : The ability of employees to collaborate with remote colleagues is now essential for most large corporations and organizations. Decades of research have identified the conditions that must be present for remote collaboration to succeed. We present a set of studies of remote collaboration within a technology company (Google) that has not only met these conditions but gone beyond them by providing ubiquitous video conferencing (VC). We looked at how well remote collaboration can now work, whether travel is still required, and what impediments still remain. We found that several factors contributed to the success of remote collaboration. Visual real-time communication via VC is ubiquitous and easy to use, VC is integrated with calendar software, and most Google employees have laptops with VC capability. Collaborative tools such as Google Docs, e-mail, and instant messaging make working together, sharing information, and keeping in touch easy. Finally, there is a culture of trust and sharing within Google. We also found that initial face-to-face meetings remain crucial for enhancing subsequent remote interactions. There were two findings of particular interest. First, VC has completely replaced audio conferencing for internal company communications. Second, video portals (always-on video connections between two or more locations) have sprung up spontaneously throughout Google. We categorize their use into four different styles of interaction and describe how they can be effective not only in facilitating communication but also in providing presence and status information, helping to establish mutual trust and common ground, and preventing misunderstandings. Video portals reduce the behavioral costs of communication and for the first time allow tightly coupled remote work to succeed. Although there are some lingering problems in technology-mediated distributed meetings, a combination of a collaborative culture with appropriate infrastructure, software, and access to technology can radically narrow the gap between colocated and remote collaboration.